A new method to determine the new C-Met inhibitor "Cabozantinib" in dosage form and human plasma via micelle-enhanced spectrofluorimetry. Issue 51 (5th June 2015) - Darwish, Hany W.; Abdelhameed, Ali S.; Bakheit, Ahmed H.; Alanazi, Amer M.
<x xml:space="preserve">Abstract</x> A highly sensitive and simple micelle-enhanced spectrofluorimetric method was developed for the determination of cabozantinib (CBZ) in its pharmaceutical formulation and spiked human plasma without any derivatization.